Successful management of Babesia bigemina infection in a transition cow - Venkatesan, M; Venkatesh, Athmakur; Latchumikanthan, A; Velusamy, R; Premalatha, N (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A pluriparous crossbred Jersey cow in early lactation was reported to the Veterinary Clinical Complex, Orathanadu with the history of anorexia, dull and depressed, coffee coloured urine and sternal recumbency for 3 days. On physical examination mucous membranes were slightly icteric, prescapular lymph node was of optimal size and presence of ticks on the surface of the body. Clinical examination revealed subnormal temperature (36.70 C), heart rate - 85 bpm, respiratory rate – 41 bpm (Tachypnoea). Hematology revealed PCV 51%, Hb – 5.2 g /dl and RBC – 3.2 mill/ cumm. Animal was treated with diminazene aceturate (Berenil® MSD Pvt. Ltd.,) @3.5 mg per kg body weight administered deep IM single dose, tranxanemic acid 10 ml IM, oxytetracycline @ 20 mg/ kg IV and supportive therapy for 5 days. Clinical improvement was observed on 7th day of treatement. This present case report describes successful management of Babesia bigemina infection in a transition cow.